The parental psychological distress caused by separation from their critically ill child during the COVID-19 pandemic: A tale of two cities - Camporesi, Anna; Abecasis, Francisco; Torres, Erica M.; Zoia, Elena; Izzo, Francesca; Ferrario, Stefania; Melloni, Elisa Maria Teresa (Frontiers in Pediatrics, 2022)
Introduction: A child’s critical illness is a stressful event for the entire family, causing significant emotional distress among parents and changes to family functioning. The SARS-CoV-2 pandemic has abruptly caused modifications in visitation policies of PICUs in many countries. We hypothesized that caregivers with no or severely restricted access to PICUs would demonstrate elevated psychological distress compared to those who had limitless access to PICU. Methods: Sociodemographics variables, levels of psychological distress, ratings of family functioning and ability to cope with stressful events were collected with an online survey in a group of caregivers after their child hospitalization. Ratings of psychological distress were compared between caregivers with no/severely restricted (NA) and with limitless access (LA) to PICUs. Results: measures of depression, anxiety and global severity index of psychological distress (GSI) were significantly higher in NA caregivers compared to LA. Among demographic characteristics of the sample only gender influenced the severity of psychological symptoms: females showed an increased score on levels of somatization, depression, anxiety and GSI. Avoidant coping style positively correlated with measures of depression. Univariate GLM analyses of the effects of sex, age, visitation policies of PICUs and score of avoidant coping strategies on measures of psychological distress confirmed a significant univariate effect of no access to PICUs on parents’ psychopathological scores. Conclusions: Restrictions imposed to visitation policies in PICU during the pandemic negatively impacted on families’ psychological well-being. A balance between safety of patients, families and health care professionals and meeting needs of families is of utmost importance.